Indirect 3D Printing of an Inflatable Wing for Small UAVS Reinforced with 3D Hexagonal Diamond Structures - Tan, Yu En (2016)
Small UAVs provide beyond-line-of-sight situational awareness to frontline troops and minimize unnecessary loss of lives. Small UAVs are carried into the field and launched manually. Inflatable wing is a potential way to increase the packing efficiency of small UAVs and reduce the load on troops. A new inflatable wing design is described in this article which addresses some of the problems encountered in existing designs. The new design can reduce weight and complexity while increasing aerodynamic performance. An indirect 3D printing method to fabricate the new wing was tested and a 3D hexagonal diamond structure was produced.